Sagot :
Answer:
Replace f(x) with y.
[tex]y= \: x2−10x \: + \: 25y= \: x \: 2-10x+25[/tex]
To find the roots of the equation, replace y with 0 and solve.
[tex]\green{\boxed{\tt0=x2−10x+25}}[/tex]
Rewrite the equation as x2−10x+25=0.
[tex]\green{\boxed{\tt \: x2−10x+25=0}}[/tex]
Factor using the perfect square rule.
[tex]\green{\boxed{\tt(x−5)2=0}}[/tex]
Set x−5 equal to 0 and solve for x.
[tex]\green{\boxed{\tt \: x=5}}[/tex]
The solution is the result of x−5=0.
[tex]\red{\boxed{\tt \: x=5}}[/tex]